2009
DOI: 10.1146/annurev-astro-082708-101816
|View full text |Cite
|
Sign up to set email alerts
|

Teraelectronvolt Astronomy

Abstract: Ground-based γ-ray astronomy, which provides access to the TeV energy range, is a young and rapidly developing discipline. Recent discoveries in this waveband have important consequences for a wide range of topics in astrophysics and astroparticle physics. This article is an attempt to review the experimental status of this field and to provide the basic formulae and concepts required to begin the interpretation of TeV observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
290
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(300 citation statements)
references
References 145 publications
(128 reference statements)
4
290
0
Order By: Relevance
“…De Angelis et al 2008;Hinton & Hofmann 2009). The majority of them are BL Lac objects, in particular those with the synchrotron bump peaking in the UV/X-ray band (highly peaked BL Lac, HBLs, Padovani & Giommi 1995).…”
Section: Introductionmentioning
confidence: 99%
“…De Angelis et al 2008;Hinton & Hofmann 2009). The majority of them are BL Lac objects, in particular those with the synchrotron bump peaking in the UV/X-ray band (highly peaked BL Lac, HBLs, Padovani & Giommi 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of the blazar Mrk 421 in the VHE regime (Punch et al 1992), many new detections of AGNs by different experiments have been reported (see, e.g. Horns 2008;Hinton & Hofmann 2009, for reviews). Strong flux variations on different timescales were observed from many AGNs.…”
Section: Introductionmentioning
confidence: 99%
“…By extrapolating measured energy fluxes [ 76] at TeV energies (e.g. [79,80]) assuming a spectral index of E −2 this flux would have been detected with more than 5σ significance, even after penalizing for the large number of trials. Furthermore, making conservative assumptions for median exposure targets one can exclude a photon flux greater than 1.44 eV cm −2 s −1 with 5σ significance.…”
Section: (Left)mentioning
confidence: 99%